Non-Muslim Sebagai Subjek Hukum Islam dalam Konsep Mukallaf - Zainuddin Puteh; Faisar Ananda Arfa (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2022)
Abstract: The appointment of the Prophet Muhammad Shalla Allahu 'Alaihi Wa Sallam as an Apostle who brought revelations with legal dimensions, addressed to all humans, including unbelievers. The position of the infidels as mukallaf can be seen from the perspective of the da'wah community, not the ijabah community who accept and justify the teachings of the Apostle as believers. However, even though they are mukallaf, unbelievers are also seen as not fulfilling as legal subjects in the law of worship, because of their disbelief. Unbelief is seen as a barrier to the validity of worship. This study uses the doctrinal method. The data is obtained through the treasures of Islamic law. The results of the study found that non-Muslims are also legal subjects in muamalah matters. Islamic law can be fully enforced against infidels, because disbelief is not a barrier (mani') the fulfillment of elements as legal subjects for infidels, so that rights that are mu'amalah should not be ignored, especially in the area of application of Islamic law.Abstrak: Pengangkatan Nabi Muhammad Shalla Allahu ‘Alaihi Wa Sallam sebagai Rasul yang membawa wahyu berdimensi hukum, ditujukan kepada seluruh manusia, termasuk orang kafir. Kedudukan orang kafir sebagai mukallaf bisa dilihat dari segi ummat dakwah, bukan ummat ijabah yang menerima dan membenarkan ajaran Rasul sebagaimana orang mukmin. Namun, meskipun sebagai mukallaf, orang kafir juga dipandang tidak memenuhi sebagai subyek hukum dalam hukum ibadah, karena kekafirannya. Kekafiran dipandang sebagai penghalang dalam keabsahan ibadah. Kajian ini menggunakan metode doktrinal. Data diperoleh melalui khazanah hukum Islam. Hasil penelitian ditemukan bahwa non muslim juga sebagai subjek hukum dalam persoalan mua’amalah. Hukum Islam dapatdiberlakukan penuh terhadap orang kafir, karena kekafiran bukan sebagai penghalang (mani’) terpenuhinya unsur sebagai subyek hukum bagi orang kafir, sehingga hak-hak yang bersifat mu'amalah tidak boleh diabaikan khsusnya di wilayah pemberlakuan hukum Islam.